Pengetahuan Kesehatan Reproduksi dan Menikah Dini pada Remaja Putri - Choirunisa Giska Adelia; Sulistiawati Sulistiawati (Oksitosin : Jurnal Ilmiah Kebidanan, 2023)
Early marriage is a marriage carried out by a couple under age of 19 years. Indonesia is a country that ranks 37th in the world for early marriages. In the scope of countries in ASEAN, Indonesia ranks second after Cambodia. Teenage girl tend to dominate more in the increasing number of early marriage. This early marriage has risks to women's reproductive health. Therefore, the importance of knowledge about reproductive health and early marriage in teenage girls. This study aim to review some research in form of literature of reproductive health and early marriage in teenage girls. Research method used literature review from Pubmed, Scincedirect, and and various research articles and case reports in Indonesian and English. There are total of 8 literatures that fit on this literature review. The results regarding the knowledge of teenagers on reproductive health, the factors that influence early marriage, and the effects of early marriage teenagers. Factor about lack of knowledge that influence the occurrence of early marriage. Efforts need to be made to increas knowledge regarding reproductive health and early marriage effectively, such as campaigns on these two matters through social media used by teenagers.